Deep Sclerectomy With Mitomycin C and Injectable Cross-linked Hyaluronic Acid Implant: Long-term Results. Issue 6 (June 2016) - Bettin, Paolo; Di Matteo, Federico; Rabiolo, Alessandro; Fiori, Marina; Ciampi, Carlo; Bandello, Francesco
Abstract : Purpose: To evaluate the long-term efficacy and safety of deep sclerectomy (DS) augmented with mitomycin C (MMC) and injectable cross-linked hyaluronic acid implant (Healaflow) in medically refractory glaucoma patients. Materials and Methods: Our study included 96 eyes of 83 consecutive patients with open-angle glaucoma undergoing MMC-DS with injectable cross-linked hyaluronic acid implant. Mean follow-up was 28.6±20.0 months. Variables analyzed were: intraocular pressure (IOP), best-corrected visual acuity, mean number of antiglaucomatous drugs, execution of postoperative maneuvres (goniopuncture, bleb needling, and laser lysis of scleral flap sutures). Tonometric success was defined by 2 different thresholds, specifically IOP⩽21 mm Hg (criterion A) and ⩽15 mm Hg (criterion B). The procedure was defined as a qualified success if reached with medication and as a complete success if reached without. Results: For criterion A, qualified and complete success rates were 96% and 94%, respectively, at 12 months, 95% and 92% at 24 months, and 92% and 89% at 36 months. For criterion B, qualified and complete success rates were 75% and 75%, respectively, at 12 months, 62% and 60% at 24 months, and 59% and 58% at 36 months. Goniopuncture was performed in 56 eyes (58%), bleb needling with 5-fluorouracil injection in 4 eyes (5.1%), and laser release of scleral flap sutures in 4 eyes (4%). Six eyes required additional filtering surgery. Conclusion: DS with Healaflow and MMC seems to be an effective and safe technique to lower IOP in patients affected by open-angle glaucoma, with few postoperative complications.